Intradural Extramedullary Nerve Sheath Myxoma of the Cervical Spine: A Case Report and Review of Literature - Xu, Fangfang; Jin, Ying; Li, Qian; Dong, Fei; Lu, Liangji; Cui, Qingfeng; Wang, Chao (Frontiers in Surgery, 2022)
Background: Nerve sheath myxoma is a rare benign soft tissue tumor. Intraspinal nerve sheath myxomas are rare. Only 8 cases of intraspinal nerve sheath myxoma have been reported to date, and no case of nerve sheath myxoma has been reported in the cervical spinal canal. Herein we reported the first case of intradural extramedullary nerve sheath myxoma in the cervical spinal canal in a 57-year-old man, including its complete clinical course and radiological findings. Case Presentation: A 57-year-old male patient had presented with numbness in his left finger without any obvious inducement for three years. Computed tomography (CT) and contrast-enhanced magnetic resonance imaging (MRI) of the spine were performed. Based on the radiological examinations, a diagnosis of schwannoma was initially made. However, nerve sheath myxoma was finally confirmed by histopathological and immunohistochemical examinations. Complete tumor excision at the C1-2 level was performed. Then, the patient recovered well and the numbness of his left finger disappeared during the later follow-up after the surgery. Conclusion: Nerve sheath myxoma should receive diagnostic con¬sideration for an extramedullary subdural lesion that is a clear boundary mass characterized by isointensity on T1-weighted images, heterogeneous intensity on T2-weighted images, peripheral obvious enhancement, and a growing tendency to the intervertebral foramen.